Elucidating Ion Transport Phenomena in Sulfide/Polymer Composite Electrolytes for Practical Solid-State Batteries - Oh, Kyeong‑Seok; Lee, Ji Eun; Lee, Yong‑Hyeok; Jeong, Yi‑Su; Kristanto, Imanuel; Min, Hong‑Seok; Kim, Sang‑Mo; Hong, Young Jun; Kwak, Sang Kyu; Lee, Sang‑Young (Nano-Micro Letters, 2023)
Despite the enormous interest in inorganic/polymer composite solid-state electrolytes (CSEs) for solid-state batteries (SSBs), the underlying ion transport phenomena in CSEs have not yet been elucidated. Here, we address this issue by formulating a mechanistic understanding of bi-percolating ion channels formation and ion conduction across inorganic-polymer electrolyte interfaces in CSEs. A model CSE is composed of argyrodite-type Li6PS5Cl (LPSCl) and gel polymer electrolyte (GPE, including Li+-glyme complex as an ion-conducting medium). The percolation threshold of the LPSCl phase in the CSE strongly depends on the elasticity of the GPE phase. Additionally, manipulating the solvation/desolvation behavior of the Li+-glyme complex in the GPE facilitates ion conduction across the LPSCl-GPE interface. The resulting scalable CSE (area = 8 × 6 (cm × cm), thickness 40 μm) can be assembled with a high-mass-loading LiNi0.7Co0.15Mn0.15O2 cathode (areal-mass-loading = 39 mg cm–2) and a graphite anode (negative (N)/positive (P) capacity ratio = 1.1) in order to fabricate an SSB full cell with bi-cell configuration. Under this constrained cell condition, the SSB full cell exhibits high volumetric energy density (480 Wh Lcell−1) and stable cyclability at 25 °C, far exceeding the values reported by previous CSE-based SSBs. Highlights: 1 Mechanistic understanding of ion transport phenomena in composite solid-state electrolytes (CSEs) for practical solid-state batteries is conducted. 2 Percolation threshold formation of the inorganic (LPSCl) phase in the CSEs depends on elasticity of the gel polymer electrolyte (GPE) phase. 3 Manipulating the solvation/desolvation behavior of the GPE phase facilitates ion conduction across the LPSCl-GPE interfaces.